THE CRUCIAL FUNCTION OF FOREIGNER TALK IN ACQUIRING L2 - Kristanti Ayuanita (IAIN MADURA, 2013)
Native speaker will do a negotiation of language they have in order to make the foreigner understand more about what they are saying.I is one of the input to the foreigner or learner in absorbing the language. This way is called the Foreigner Talk, in which the native speaker tries to use the simplified variety of language and some check and confirmation to convince the language they utter so the foreigner can understand the language they convey easily. Some studies done by De Lima, Freed, Long, and Ulichny have investigated Foreigner Talk in non educational contexts to find out what the parameters of FT simplification are and how the adjusted input facilitates NS-NNS communication.